Strategi Pembangunan Kontekstual Terpadu Sektor Perkebunan, Pertanian,Peternakan, Perikanan Dan Industrialisasi Pengolahan Menjadi Pakan Ternak dan Ikan - Sufian Hamim; Lolita Vianda (UIR Press, 2019)
The research objective is to analyze and explain the development of development areas in Indragiri Hilir Regency with an integrated contextual development strategy in the Plantation, Agriculture, Animal Husbandry, Fisheries, and Industrialization Processing into Animal / Fish Feed. The research methods used through field research strengthen each other's quantitative and qualitative approaches, namely survey research exploring primary and secondary data information sources, FGDs and joint community studies in the areas of production centers for plantations, agriculture, animal husbandry, fisheries and industrialization, as an effort to synergize production, post-processing harvest to market the product. Indragiri Hilir Regency has a potential of 45,040.8 tons per year of raw materials for the production of poultry feed, animal feed and fish feed. Integration and complementary development of all sectors of plantation, agriculture, animal husbandry, fishery and industrialization, upstream and downstreaming are integrated into an integrated development center with a strategic, integrated and holistic development management. After post-harvest, farmers are also expected to be able to carry out post-harvest businesses with advanced product packaging and processing processes, for example animal feed and fish feed, so that they are more economical and have added value.